Branding Coffee Shop Premium di Era Digital: Analisis Customer-Based Brand Equity Keller pada Tiga Coffee Shop Premium di Surabaya - Buana, Sekar Fatima Permata; Rahmawati, Aulia (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study aims to analyze the branding strategies of three premium coffee shops in Surabaya—Drama Coffee, Alura Coffee, and Coffee at Louis—using Keller’s Customer-Based Brand Equity (CBBE) framework. The CBBE model consists of four main stages: brand salience, brand meaning, brand response, and brand resonance. A qualitative descriptive method was applied, with data collected through in-depth interviews, observation, documentation, and literature review. The findings indicate that all three coffee shops successfully built consumer-based brand equity but employed different approaches. Drama Coffee emphasizes storytelling and a relaxed atmosphere as a space for emotional expression, Alura Coffee highlights a warm and aesthetic “second home” identity, while Coffee at Louis focuses on delivering an authentic “Australian-style coffee experience” with premium quality. The key similarity lies in the consistency of brand identity and the use of Instagram as the main branding channel, while the differences emerge in each shop’s unique positioning according to its target market. This research underscores the importance of differentiated branding strategies in fostering consumer loyalty and emotional attachment.
Keywords: Branding; CBBE; Coffee Shop; Communication Strategy; Instagram